2023
DOI: 10.1371/journal.ppat.1011242
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatic natural killer cell function via the TIGIT receptor in schistosomiasis-induced liver fibrosis

Abstract: Schistosomiasis is a zoonotic parasitic disease. Schistosoma japonicum eggs deposited in the liver tissue induce egg granuloma formation and liver fibrosis, seriously threatening human health. Natural killer (NK) cells kill activated hepatic stellate cells (HSCs) or induce HSC apoptosis and inhibit the progression of liver fibrosis. However, the function of NK cells in liver fibrosis caused by S. japonicum infection is significantly inhibited. The mechanism of this inhibition remains unclear. Twenty mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Many studies on the mechanism of schistosomiasis-induced liver fibrosis have concentrated on the control of hepatic stellate cells activated by immune cells, such as NK cells [ 43 ], macrophages [ 44 ], eosinophils [ 45 ], and γδT cells [ 46 ]. However, less attention has been paid to hepatocyte-regulating hepatic stellate cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on the mechanism of schistosomiasis-induced liver fibrosis have concentrated on the control of hepatic stellate cells activated by immune cells, such as NK cells [ 43 ], macrophages [ 44 ], eosinophils [ 45 ], and γδT cells [ 46 ]. However, less attention has been paid to hepatocyte-regulating hepatic stellate cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the suppressive effect of TIGIT on CD226-mediated activation of NK cells [59], TIGIT deficiency can suppress parasite (Schistosoma japonicum) infectioninduced liver fibrosis [83]. A cellular mechanism study showed that NK cells from TIGITdeficient mice compared to NK cells from wild-type mice can induce more co-cultured HSC apoptosis [83].…”
Section: Tigitmentioning
confidence: 99%